Penerapan Pijat Bayi pada Bayi Berat Lahir Rendah: Laporan Kasus: Application of Infant Massage in Low Birth Weight Infants: A Case Report - Prima Yoselina; Puspa Sari; Linda Andriani; Mechi Silvia Dora (NERS Jurnal Keperawatan, 2024)
Low Birth Weight (LBW) infants are babies with a birth weight of less than 2,500 grams. The incidence rate of LBW in the world reaches 15% and every year it is estimated that 20 million babies are born with LBW. Basic Health Research Data in 2018 shows that the prevalence of infants with LBW in Indonesia is 6.2% and the cause of neonatal death due to LBW is 35.3%. Baby massage is one of the nursing interventions in LBW to overcome respiratory disorders and increase the baby's weight. This study aims to explain the case of applying baby massage with LBW. This research method is a case report on Mrs. W's baby who was treated in the NICU room of Pariaman Hospital. The report is carried out based on the stages of nursing care, namely assessment, nursing diagnosis, intervention, implementation, and evaluation of nursing. Baby massage is given for 4 days in the morning every day on Mrs. W's baby. After massage therapy, the baby becomes more comfortable because the baby's blood circulation is smooth, the baby's breathing becomes optimal, and the baby's weight increases. This shows that baby massage provides benefits to babies, especially LBW. It is hoped that baby massage can be one of the independent actions for nurses or health workers in providing nursing care to babies with LBW.